Q: What is x divided by 2 x2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

x= x2/x= x

0.5

Answer: (x-2) (x2-5x+6)/(x-3) =(X-3)X(X-2)/(X-3) <-You factor the expression (x2-5x+6) and get (x-3)(x-2) =(X-2) <-The (x-3)'s in the numerator and denominator cancel each other out (because an expression divided by the same expression equals one) and thus you are left with (x-2).

Related questions

The remainder is 8. (x2 + 4)/(x - 2) = (x + 2) + 8/(x - 2) or x2 + 4 = (x - 2)(x + 2) + 8

4

X2 (X squared)

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

The antiderivative of x/(x2-1) is ln(x2-1)/2. Proof: (ln(x2-1)/2)' = (1/(x2-1))*(x2-1)'/2=1/(x2-1)*(2x/2)=x/(x2-1).

if x2 = 5 the value of x has to be 5 divided by 2 which is 2.5 x = 2.5

2

x= x2/x= x

0.5

-2

If your doing exponents (x squared) the answer is x. If your multiplying( X times 2) the answer is 2

Answer: (x-2) (x2-5x+6)/(x-3) =(X-3)X(X-2)/(X-3) <-You factor the expression (x2-5x+6) and get (x-3)(x-2) =(X-2) <-The (x-3)'s in the numerator and denominator cancel each other out (because an expression divided by the same expression equals one) and thus you are left with (x-2).